Small scale eucalyptus cultivation and its socioeconomic impacts in Ethiopia: A review of practices and conditions - Asabeneh Alemayehu; Yoseph Melka (Trees, Forests and People, 2022)
Plantation of Eucalyptus has been recently expanding into productive farmlands, homesteads, farm boundaries, grazing lands and open communal lands in Ethiopia. This review addresses the trends and extents of Eucalyptus planting, identifies factors affecting Eucalyptus planting decisions, and assesses the socioeconomic and ecological contributions of Eucalyptus for the smallholder farmers and consumers in Ethiopia. It also examines planting and management practices as well as policies and regulations on Eucalyptus production. Smallholders are mainly motivated to plant and convert their productive farm plots into Eucalyptus due to the growing demand for wood and wood products as well as the associated increase in the price of its products (mainly poles). The decisions by smallholder farmers are influenced by several socioeconomic and demographic factors such as age, educational status, family size, income, farm size, road availability, nursery ownership, land productivity and marginal land to agriculture. It is also affected by institutional factors including tenure security, access to credit and access to market, and psychological factors like perception of risk and attitude towards Eucalyptus species. Eucalyptus has a diverse socioeconomic and ecological contribution to the livelihood of society. Under current demand and market conditions, planting Eucalyptus provides a far better return on investment than alternative land uses (crop production and animal keeping) for the smallholder tree cultivators. Eucalyptus helps households to become wood self-sufficient and provides considerable cash income. The income percentage contribution of Eucalyptus was ranked as a second major source of rural household income following crop production in many parts of the country. Now Eucalyptus is commonly planted as woodlots replacing productive agricultural systems, but with the absence of any support. The species is a great asset for planters and contributes to rural development and poverty reduction in Ethiopia though it is criticized for its water depletion, soil nutrient loss and its inability to support biodiversity and wild animals. However, its positive impacts could outweigh the negative ones if it is planted on the right sites with good management planning and proper tending operations. Therefore, decisions about the species solely based on the perceived negative ecological impacts are not sensible; rather focusing on its economic, social and ecological impacts on the local community is highly imperative and essential for mutual benefits. Additionally, selection of more valuable tree species, proper land use planning, extension support and implementation of the formulated regulations at the grass-root level is highly recommended.